2008
DOI: 10.1623/hysj.53.3.640
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of non-parametric and parametric water temperature models on the Nivelle River, France

Abstract: Water temperature is an important abiotic variable in aquatic habitat studies and may be one of the factors limiting the potential fish habitat (e.g. salmonids) in a stream. Stream water temperatures are modelled using statistical approaches with air temperature and streamflow as exogenous variables in the Nivelle River, southern France. Two different models are used to model mean weekly maximum temperature data: a non-parametric approach, the k-nearest neighbours method (k-NN) and a parametric approach, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 51 publications
0
26
0
1
Order By: Relevance
“…For water resource and fisheries managers, it may be important to include other variables that may have an impact on the thermal regime of rivers, such as air temperature and flow. For this reason, the PAR method was extended by Benyahya et al (2007b) to incorporate other input variables (e.g., air temperature, streamflow) called exogenous variables and therefore the PAR model become a PARX model. A PARX model representing the water temperature series may be written in the following form…”
Section: Periodic Autoregressive Modelsmentioning
confidence: 99%
“…For water resource and fisheries managers, it may be important to include other variables that may have an impact on the thermal regime of rivers, such as air temperature and flow. For this reason, the PAR method was extended by Benyahya et al (2007b) to incorporate other input variables (e.g., air temperature, streamflow) called exogenous variables and therefore the PAR model become a PARX model. A PARX model representing the water temperature series may be written in the following form…”
Section: Periodic Autoregressive Modelsmentioning
confidence: 99%
“…air temperature, solar radiation, conduction from soil, etc.) and anthropogenic disturbances of the natural thermal regime such as deforestation and hydroelectric development (Gras, 1969;Beschta et al, 1987;Benyahya et al, 2008). In recent years a number of studies have identified global warming as another major influence of water temperature (Sinokrot et al, 1995;Webb, 1996;Mohseni et al, 1998Pedersen and Sand-Jensen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Daily air temperature and prior 7-day air temperature were important predictors in other stream temperature models [DeWeber and Wagner, 2014;Jackson et al, 2018]. This 7-day lag may result from a combination of factors including water flow from upstream, conductive heating from the ground which is slow to transfer heat and averages temperatures over extended periods, and through delayed surface and shallow ground-water inputs [Benyahya et al, 2008;Webb et al, 2010].…”
Section: Meteorological and Landscape Datamentioning
confidence: 98%